8-(5-x)=-3(x+4)

Simple and best practice solution for 8-(5-x)=-3(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-(5-x)=-3(x+4) equation:


Simplifying
8 + -1(5 + -1x) = -3(x + 4)
8 + (5 * -1 + -1x * -1) = -3(x + 4)
8 + (-5 + 1x) = -3(x + 4)

Combine like terms: 8 + -5 = 3
3 + 1x = -3(x + 4)

Reorder the terms:
3 + 1x = -3(4 + x)
3 + 1x = (4 * -3 + x * -3)
3 + 1x = (-12 + -3x)

Solving
3 + 1x = -12 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
3 + 1x + 3x = -12 + -3x + 3x

Combine like terms: 1x + 3x = 4x
3 + 4x = -12 + -3x + 3x

Combine like terms: -3x + 3x = 0
3 + 4x = -12 + 0
3 + 4x = -12

Add '-3' to each side of the equation.
3 + -3 + 4x = -12 + -3

Combine like terms: 3 + -3 = 0
0 + 4x = -12 + -3
4x = -12 + -3

Combine like terms: -12 + -3 = -15
4x = -15

Divide each side by '4'.
x = -3.75

Simplifying
x = -3.75

See similar equations:

| t/2-7=6 | | Log(a)4=8 | | y=x(x)-6x+7 | | 13(y+4)=65 | | 24=3(2-1x) | | 13x+11=12x+4 | | 96=12s | | 8+6x=9x-13 | | 14x-96.2=4.8 | | 4=3.4/(x-3.4) | | -k^2-6k-8=0 | | 2t-8=42-3t | | (11-5x)=(4x+y) | | 13x-11=12x+4 | | yx+2x=3 | | 20=6k+8 | | 48=5(2y+3) | | b/7-2=3 | | tanx/2=1 | | 4x-30=5x-6 | | x+5+117=180 | | 8n^2-61n-24=0 | | 2x-(16/x^2)=0 | | X40/30 | | http://media.education2020.com/evresources/643-05-06-00-00_files/i0240000.jpg | | 7w+2=3w+38 | | 14c^-3/7c^-9 | | 12-3(x-5)=2(x-4)+15 | | x/26=32 | | 21n^2+46n+24=0 | | z/12=25 | | x/24=38 |

Equations solver categories